Reconciling the conservation of the purple swamphen (Porphyrio porphyrio) and its damage in Mediterranean rice fields through sustainable non-lethal techniques - Rubén Moreno-Opo; Josep Piqué (PeerJ, 2018)
Resolving human–wildlife conflicts requires the assessment and implementation of appropriate technical measures that minimize negative impacts on socio-economic uses, including agriculture, and ensure the adequate protection of biological diversity. Rice paddies are widely distributed in the western Mediterranean region. Because of their high productivity, they can be a good habitat for waterbirds, including the purple swamphen Porphyrio porphyrio, particularly in areas where natural wetlands have been removed or reduced. As a result of its population growth, there have been increasing levels of damage caused by this species in rice fields due to stem-cutting and opening of bald patches in rice fields. With the aim of reducing damage, we evaluated the effectiveness of passive and active measures that would limit access to rice fields and deter/scare away purple swamphens in affected areas of the Ebro Delta (NE Spain). We selected the techniques according to the growth phase of rice and the activity of birds in the rice fields (perimeter fences and clearing vegetation around the rice plots during sprouting and growing phases, and falconry at maturation). There were positive results during the sprouting and growing phases thanks to fences and clearing vegetation, reducing the affected area by 37.8% between treatment and control plots. This would mean an economic savings of 18,550 €/year in compensation payments by regional administrations including the investment in implementing and maintaining passive protection measures. Active deterrence through falconry did not reduce the level of damage. The analysis of purple swamphen home range, activity centers (centroids), and the proportion of locations in and outside of rice fields showed no differences before and after dissuasive practices. These results were influenced by multiple concurrent factors including weather, the structural configuration of the rice plots and their location. In summary, we recommend the establishment of protection measures (perimeter fences + clearing vegetation around the rice plots) to reduce the level of damage.